The peculiarities of labor legal relations with a family doctor in the context of healthcare reform in Ukraine - Subbot, Anatolii I.; Lysenko, Tetiana V.; Anokhin, Vadym; Mazur, Iryna; Muntian, Liliia (Edelweiss Applied Science and Technology, 2024)
According to national and international legislation, every person on the territory of Ukraine has the right to qualified medical assistance. As a result of healthcare reform in Ukraine, family doctors have started working, with whom patients conclude declarations in accordance with Ukrainian legislation. Consideration of labor legal relations with a family doctor is extremely important and relevant, as there are many problems and gaps in practice and legislative activities that require research and resolution. The full-scale invasion of Russia on the territory of our state had a negative impact on labor legal relations with family doctors. Due to hostilities, many patients have left for safer places in Ukraine or abroad. Many family doctors, who left their home and place of residence, are generally forced to seek for another place of work. These are significant drawbacks of labor law in the field of medicine, which we are currently facing in Ukraine and which require regulation and finding ways to resolve them. Therefore, consideration of theoretical and legislative material is relevant and extremely important. The purpose is to study the peculiarities of labor legal relations with a family doctor in the context of healthcare reform in Ukraine. The object is the legal basis and legislative framework, which regulate labor legal relations with a family doctor. Conducting research and summarizing qualifications, it can be said that general scientific methods, general methods, interdisciplinary methods, and specialized methods are applied. The analysis of the theoretical and legal source base, from the labor legislation, reveals ways to solve the problematic issues that family doctors face today. Incorporating positive international experience and making proposals for its further consideration and implementation in practice will make it possible to solve the current problems, taking into account all the risks. It is proposed to increase the salary of family doctors, regardless of the number of patients who have signed declarations with them. It is proposed to highlight the fundamental principles of labor activity with family doctors, which are based on the principles of legality, openness, voluntariness, normativity, transparency, control, and informativeness. The proposal is to enhance public awareness of the services of family doctors and the conclusion of declarations without being tied to the location.